Evaluation of different foot-and-mouth disease vaccination protocols in cattle in the Zambezi region of Namibia - Quan, Melvyn (University of Pretoria, 2025)
Dissertation (MSc (Veterinary Tropical Diseases))--University of Pretoria, 2025.